DIET PATTERNS IN HYPERCHOLESTEROLEMIA PATIENTS IN LEMITO DISTRICT - Santoso, Eko; Pomalango, Zulkifli B; Rahim, Nirwanto K. (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Hypercholesterolemia is one of the lipid metabolism disorders that contributes to the risk of cardiovascular disease, the leading cause of death in the world. This study aims to describe the dietary patterns of hypercholesterolemia patients in Lemito District. The research method uses an analytical observational approach with a descriptive analytical design. The study population was hypercholesterolemia patients registered at the Wonggasari I Health Center and Lemito Health Center in 2024, with a total of 52 respondents selected using the total sampling method. The results showed that the majority of respondents (53.8%) had poor dietary patterns, characterized by high consumption of saturated fat, processed foods, and sugar, and low fiber intake. Meanwhile, 46.2% of respondents showed a good diet. Social, economic, and cultural factors are challenges in implementing a healthy diet. This study suggests the need for ongoing education about healthy diets through community-based programs to increase public awareness of the importance of consuming nutritious foods. This intervention is expected to help reduce the prevalence of hypercholesterolemia and the risk of cardiovascular complications in the area.